Islamic Education Methods In The Perspective Of Imam An-Nawawi - R, Rabumas (Journal of Innovation in Research, Education and Culture (JIREC), 2023)
Based on the verses and hadiths included by Imam An- Nawawi in the book Riyadu Al-Salihin we can analyze the style of educational thought according to Imam An-Nawawi, while education according to Imam An-Nawawi consists of 19 books (themes). Of the nineteen points (the theory written by Imam An-Nawawi in the book of Riyadhush Shalihin), therefore the thoughts of Imam An-Nawawi have several points that are very important and need to be considered in Islamic education, some of which researchers take are as follows , in the book (theme) of honesty. Besides that, Imam An-Nawawi emphasized the importance of juju, being honest is a characteristic of believers, honest orders, rewards for honest people, rewards and punishments for dishonest people. Both in deed and word. The problem to be answered from this thesis which has been described is regarding the concept of Islamic education in the thought of Imam An-Nawawi which was written by the Imam. The Imam as a well-known figure among the scholars' and the Imam focuses on writing books so that people are able to understand religion correctly according to the guidance of the Prophet. The Imam collects the hadiths of the Prophet and then summarizes them as guidelines for the life of Muslims. This research is a library research with a focus on collecting, analyzing, presenting and concluding information related to the thoughts of the characters. There are two types of sources for this research, namely primary sources which come from a book written by Imam An-Nawawi on provision of knowledge entitled Riyadhush Shalihin. Then secondary sources are the results of books written by Imam An-Nawawi, PDF books, journals, and other books that are in accordance with the contents of this research.Keywords: Concept, Imam An-Nawawi, Islamic Education